Early diagnostic of malignant melanoma of the skin and of the oral mucous membrane - Rudnicka, Lidia; Olszewska, Małgorzata; Słowińska, Monika (Contemporary Oncology/Współczesna Onkologia, 2003)
Due to the increasing frequency of malignant melanoma it is crucial to detect early the malignant lesions on the basis of physical examination and noninvasive diagnostic methods. The ABCD rule for the first-step analysis of pigmentary skin lesions and ABC (DEF) rule for the subungual melanoma, as well as so called simulators of malignant melanoma are presented. The article compares the specificity and sensitivity between the physical examination, dermatoscopic features (pattern analysis, ABCD rule of Stolz, Menzies method, 7 features of melanoma), videodermatoscopic images (A (A) BCDE rule) and the fluorescent method. Even combining the methods of clinical diagnosis and dermatoscopic features are still not sufficient to detect 100% of early melanomas. Thereby repeated total body photos revealing growth/ /change of existing melanocytic nevi andthe appearance of new pigmentary lesions might be a good proposal in partial filling of the existing lack.